How Orthography Modulates Morphological Priming: Subliminal Kanji Activation in Japanese - Nakano, Yoko; Ikemoto, Yu; Jacob, Gunnar; Clahsen, Harald (Frontiers in Psychology, 2016)
The current study investigates to what extent masked morphological priming is modulated by language-particular properties, specifically by its writing system. We present results from two masked priming experiments investigating the processing of complex Japanese words written in less common (moraic) scripts. In Experiment 1, participants performed lexical decisions on target verbs; these were preceded by primes which were either (i) a past-tense form of the same verb, (ii) a stem-related form with the epenthetic vowel -i, (iii) a semantically-related form, and (iv) a phonologically-related form. Significant priming effects were obtained for prime types (i), (ii) and (iii), but not for (iv). This pattern of results differs from previous findings on languages with alphabetic scripts, which found reliable masked priming effects for morphologically related prime/target pairs of type (i), but not for non-affixal and semantically-related primes of types (ii) and (iii). In Experiment 2, we measured priming effects for prime/target pairs which are neither morphologically, semantically, phonologically nor - as presented in their moraic scripts – orthographically related, but which - in their commonly written form - share the same kanji, which are logograms adopted from Chinese. The results showed a significant priming effect, with faster lexical-decision times for kanji-related prime/target pairs relative to unrelated ones. We conclude that affix-stripping is insufficient to account for masked morphological priming effects across languages, but that language-particular properties (in the case of Japanese, the writing system) affect the processing of (morphologically) complex words.